2013
DOI: 10.5830/cvja-2013-001
|View full text |Cite
|
Sign up to set email alerts
|

Management of ischaemic stroke in the acute setting : review of the current status : review article

Abstract: Acute ischaemic stroke can be treated by clot busting and clot removal. Thrombolysis using intravenous recombinant-tissue plasminogen activator (IV r-TPA) is the current gold standard for the treatment of acute ischaemic stroke (AIS). The main failure of this type of treatment is the short time interval from stroke onset within which it has to be used for any benefit. The evidence is that IV r-TPA has to be used within 4.5 hours.Other modalities of treatment are not as effective and need more scrutiny and exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Approximately 80% of strokes are ischemic [1,2]. The standard treatment for stroke is thrombolysis, which has rather limited efficacy [3,4]. Ischemic stroke induces bloodbrain barrier (BBB) breakdown that contributes to secondary brain injury by causing cerebral edema, increasing hemorrhage, and exacerbating the inflammatory response [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 80% of strokes are ischemic [1,2]. The standard treatment for stroke is thrombolysis, which has rather limited efficacy [3,4]. Ischemic stroke induces bloodbrain barrier (BBB) breakdown that contributes to secondary brain injury by causing cerebral edema, increasing hemorrhage, and exacerbating the inflammatory response [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials with IV administration of reteplase in the setting of AIS is limited, and the results are conflicting. In a recent review , it was stated that no evidence is present showing benefit with reteplase for use in the setting of AIS. On the contrary, the Reopro Retevase Reperfusion of Stroke Safety Study (ROSIE) showed that in combination with Abciximab, intraarterial reteplase was revealed to have acceptable safety and efficacy in AIS patients within 3–24 h of symptom onset, with a disabling stroke, NIHSS score ≤16 points, and evidence of a perfusion deficit on PWI/MRI and MR angiography .…”
Section: Discussionmentioning
confidence: 99%
“…Antithrombolytic drugs are administered routinely in these stroke units hence; they have similar outcomes to the developed world [70]. These centres have gone further to institute multidisciplinary stroke care noting a reduction of inpatient mortality from 33% to 16% in one case [71]. The authors however decried the fact that the number of CT brain scans performed and referral to a tertiary hospital did not increase significantly [71].…”
Section: Action Taken In the Care Of Stroke In Sub Saharan Africamentioning
confidence: 99%
“…These centres have gone further to institute multidisciplinary stroke care noting a reduction of inpatient mortality from 33% to 16% in one case [71]. The authors however decried the fact that the number of CT brain scans performed and referral to a tertiary hospital did not increase significantly [71]. One suggestion is that a greater endeavour should be made in resource-limited settings to expand facilities to enable intravenous r-tPA treatment within the 4.5 h period following onset of stroke.…”
Section: Action Taken In the Care Of Stroke In Sub Saharan Africamentioning
confidence: 99%